(untitled) - Gillespie, James R. (Albany, N.Y., 1989)
This text for vocational-technical students emphasizes readability, organization, and hands-on activities. Sections cover the livestock industry, feeding and nutrition, animal breeding, and the production of various stock including beef cattle, poultry, llamas, and bison
Keywords: Poultry.,Livestock